Water mites from caves of the Ha Giang province, northern Vietnam (Acari: Hydrachnidia) - Pešić, Vladimir; Gerecke, Reinhard (Zootaxa, 2014)
Four species of water mites (Acari, Hydrachnidia) were collected in 2010 during an Italian speleological expedition to caves of the Ha Giang region in northern Vietnam from rimstone pools or other tiny accumulations of percolating water. Four taxa new to science are described, representing the families Torrenticolidae (Torrenticola anophthalma nov. sp., Stygotorrenticola coniseta nov. gen., nov. sp.), Limnesiidae (Raptorhydracarinae subfam. nov., Raptorhydracarus tomasini nov. gen., nov sp.) and Athienemanniidae (Africasia vietnamitica sp. nov.). Most of these taxa show striking morphological adaptations to subterranean life.